Dental Evaluation Prior to Cancer Therapy - Yong, Chee Weng; Robinson, Andrew; Hong, Catherine (Frontiers in Oral Health, 2022)
A comprehensive oral examination and dental care prior to the start of cancer therapy is the standard of care in many cancer centers. This is because good oral health will likely minimize the undesirable complications such as opportunistic infections during cancer therapy. As the considerations differ between anti-neoplastic regimens, this chapter discusses the indications and rationale when planning and executing a treatment plan for patients undergoing various cancer therapies.